The Production of Alternative Global Spaces: Walking in the City in Salman Rushdie's Novels. Issue 1 (2nd January 2018) - Roy, Madhumita; Roy, Anjali Gera
Abstract : de Certeau explicitly posits walking as a mode of resistance, which has been updated in theories of affect and posthumanism that advocate a return to the concept of the body and the human, respectively. These new theories propose a modified walker who blurs the subject–object/human–nonhuman distinction, reinforcing both a contested embodiment and an inclusive approach to the "other" in self-fashioning. Salman Rushdie, too, uses the trope of walking in the city as an altered act of resistance. Walking, an exercise in Rushdie's novels that deconstructs the autonomous bodies of walkers at the moment of their encounter with material cities, aligns itself to postanthropocentric discourses of walking. This fracturing of the autonomous bodies of walkers, however, is a result of the modified body politic and relevant to migrant figures from the Global South rather than to the provincial walkers of the Global North.